(untitled) (Journal of Orofacial Research, 2020)
Background: Polymethyl methacrylate (PMMA) has been the most commonly used material for construction of dentures since many decades. Although it has many advantages like good esthetics, accurate fit, stability in the oral environment, however lack of strength of material results in fracture. Objective: To evaluate the flexural strength of a heat-cured denture base resins with different powder/liquid (P/L) ratios. Methods: 150 acrylic samples were made using high impact denture base resin (Travelon Hi). The samples were divided into five groups based on different powder/liquid ratios (g/ml) with 30 samples in each group. The P/L ratio in Group 1 (2.2:1) was the manufacturer’s recommended ratio and was used as control. In Group 2, the ratio was 2.7:1, in Group 3, the ratio was 3.2:1, in Group 4, the ratio was 1.9:1, and Group 5 the ratio was 1.6:1. The samples were tested for flexural strength. Results: The values of flexural strength decreased significantly as the P/L ratio was increased or decreased from the control group with standard deviation 4.50, 4.15, 4.11, 4.15 and 5.59 respectively for the various groups. Conclusion: For high impact resins, the manufacturer’s recommended polymer/monomer mixing ratio should be used to obtain the appropriate strength of the material.